Integration Of Existential Intelligence And Levels Of Intellect In Strengthening Spirituality Through Islamic Education - Abu Darda; Sayyida Nafisa Al-Razi (Institut Agama Islam An-Nawawi Purworejo, 2026)
Islamic education learning in various educational institutions generally tends to focus on cognitive aspects and memorization, making it less effective in fostering students’ spirituality in a more profound and meaningful way. Although the concepts of existential intelligence and the levels of intellect have been widely discussed separately, there remains a gap in integrating both as a foundation for a holistic Islamic education learning model. This study uses the library research. The data was collected through a review of primary sources such as Howard Gardner's works Frames of Mind: The Theory of Multiple Intelligences, Intelligence Reframed: Multiple Intelligences for the 21st Century, and Ibn Sina's work An-Nafs. Secondary sources came from various journals, books, and scientific articles discussing existential intelligence and levels of Intellect. This study referred to Krippendorf's content analysis principles. The results of this study indicate that the integration of these two concepts results in a model of Islamic education learning that not only emphasizes cognitive understanding but also encourages reflection on the meaning of life, the strengthening of intellect, and the holistic development of students’ spirituality. This model is expected to assist students in developing a profound sense of spirituality and in internalizing and applying Islamic teachings in their daily lives.